2012
DOI: 10.1103/physreva.85.033638
|View full text |Cite
|
Sign up to set email alerts
|

Confinedp-band Bose-Einstein condensates

Abstract: We study bosonic atoms on the p band of a two-dimensional optical square lattice in the presence of a confining trapping potential. Using a mean-field approach, we show how the anisotropic tunneling for p-band particles affects the cloud of condensed atoms by characterizing the ground-state density and the coherence properties of the atomic states both between sites and atomic flavors. In contrast to the usual results based on the local-density approximation, the atomic density can become anisotropic. This ani… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
32
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 46 publications
0
32
0
Order By: Relevance
“…Within the local density approximation, the trap renormalizes the couplings so that they become spatially dependent [30], but this effect can be negligible if the orbitals are small compared to the length scale of the trap. In the regime of strong repulsion, the main effect of the trap is instead that it gives rise to "wedding cake" structures with Mott regions of integer filling.…”
mentioning
confidence: 99%
“…Within the local density approximation, the trap renormalizes the couplings so that they become spatially dependent [30], but this effect can be negligible if the orbitals are small compared to the length scale of the trap. In the regime of strong repulsion, the main effect of the trap is instead that it gives rise to "wedding cake" structures with Mott regions of integer filling.…”
mentioning
confidence: 99%
“…when going beyond the HA approximation. However, it was shown that anharmonicity may have important consequences when one studies p-band physics [16,21,22]. In our Letter, we demonstrate that the apparently technical and quantitatively small change of harmonically approximated on-site functions to the true orthonormal basis of Wannier states may substantially change the phase diagram and many-body physics in a nonperturbative way.…”
mentioning
confidence: 80%
“…Note that our potential does not take into account the slowly spatially varying harmonic trap typically present in experiments, which may affect the properties of p-band states [22]. In the following, we shall assume a uniform filling of sites, thus explicitly excluding the additional trapping.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This introduces new degrees of freedom for the bosons, e.g. that the orbitals can point in different directions, which leads to anisotropic tunneling and interactions [194].…”
Section: Extended Bose-hubbard Modelsmentioning
confidence: 99%